Developmental changes in brain activity of heterozygous Scn1a knockout rats - Tahara, Mayu; Higurashi, Norimichi; Hata, Junichi; Nishikawa, Masako; Ito, Ken; Hirose, Shinichi; Kaneko, Takehito; Mashimo, Tomoji; Sakuma, Tetsushi; Yamamoto, Takashi; Okano, Hirotaka James (Frontiers in Neurology, 2023)
Introduction Dravet syndrome (DS) is an infantile-onset developmental and epileptic encephalopathy characterized by an age-dependent evolution of drug-resistant seizures and poor developmental outcomes. Functional impairment of gamma-aminobutyric acid (GABA)ergic interneurons due to loss-of-function mutation of SCN1A is currently considered the main pathogenesis. In this study, to better understand the age-dependent changes in the pathogenesis of DS, we characterized the activity of different brain regions in Scn1a knockout rats at each developmental stage. Methods We established an Scn1a knockout rat model and examined brain activity from postnatal day (P) 15 to 38 using a manganese-enhanced magnetic resonance imaging technique (MEMRI). Results Scn1a heterozygous knockout (Scn1a+/−) rats showed a reduced expression of voltage-gated sodium channel alpha subunit 1 protein in the brain and heat-induced seizures. Neural activity was significantly higher in widespread brain regions of Scn1a+/− rats than in wild-type rats from P19 to P22, but this difference did not persist thereafter. Bumetanide, a Na+-K+-2Cl− cotransporter 1 inhibitor, mitigated hyperactivity to the wild-type level, although no change was observed in the fourth postnatal week. Bumetanide also increased heat-induced seizure thresholds of Scn1a+/− rats at P21. Conclusions In Scn1a+/− rats, neural activity in widespread brain regions increased during the third postnatal week, corresponding to approximately 6 months of age in humans, when seizures most commonly develop in DS. In addition to impairment of GABAergic interneurons, the effects of bumetanide suggest a possible contribution of immature type A gamma-aminobutyric acid receptor signaling to transient hyperactivity and seizure susceptibility during the early stage of DS. This hypothesis should be addressed in the future. MEMRI is a potential technique for visualizing changes in basal brain activity in developmental and epileptic encephalopathies.